2021
DOI: 10.1021/acs.jafc.1c05880
|View full text |Cite
|
Sign up to set email alerts
|

Role of Grape-Extractable Polyphenols in the Generation of Strecker Aldehydes and in the Instability of Polyfunctional Mercaptans during Model Wine Oxidation

Abstract: Polyphenolic fractions from Garnacha, Tempranillo, and Moristel grapes were reconstituted to form model wines of identical pH, ethanol, amino acid, metal, and varietal polyfunctional mercaptan (PFM) contents. Models were subjected to a forced oxidation procedure at 35 °C and to an equivalent treatment under strict anoxia. Polyphenolic profiles significantly determined oxygen consumption rates (5.6–13.6 mg L –1 day –1 ), Strecker aldehyde (SA) accumulation (ratios m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Polyphenols and especially flavanols are readily oxidisable compounds that modulate the presence of desirable (4-methyl-4-mercaptopentanone (4MMP), 3-mercaptohexanol (3MH) or 3-mercaptohexyl acetate (MHA)) and undesirable (hydrogen sulphide (H 2 S)) nucleophilic volatile polyfunctional mercaptans (PFMs). 17 During the wine exposure to oxygen, reactive chemical species in the form of quinones are formed and are therefore available to react with nucleophilic compounds. 18 Phenolic oxidation processes are thus involved in removing these sulfur-containing nucleophilic species.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols and especially flavanols are readily oxidisable compounds that modulate the presence of desirable (4-methyl-4-mercaptopentanone (4MMP), 3-mercaptohexanol (3MH) or 3-mercaptohexyl acetate (MHA)) and undesirable (hydrogen sulphide (H 2 S)) nucleophilic volatile polyfunctional mercaptans (PFMs). 17 During the wine exposure to oxygen, reactive chemical species in the form of quinones are formed and are therefore available to react with nucleophilic compounds. 18 Phenolic oxidation processes are thus involved in removing these sulfur-containing nucleophilic species.…”
Section: Introductionmentioning
confidence: 99%
“…The lower accumulation rates found in white and rosé wines were not expected according to the hypotheses formulated in previous works [ 5 , 23 ]. Whites and rosés have zero or negligible amounts of anthocyanin [ 24 ], which are the molecules suggested as the main consumers of aldehydes [ 5 , 25 ] or sacrificial antioxidants [ 23 ]. However, a lower number of phenolic compounds in general could explain a lower amount of Strecker aldehyde precursor quinones.…”
Section: Resultsmentioning
confidence: 45%
“…Higher O 2 consumption rates, related to higher amounts of delphinidin [ 28 ], Ref. [ 23 ] could be associated with quinones more likely to give the Strecker reaction. Delgado et al demonstrated under extreme conditions (1 h, 180 °C) that polyphenols with hydroxyl groups in the ortho position (as delphinidin) favored the formation of phenylacetaldehyde [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent papers in which a set of red wines [12] and synthetic wines containing polyphenols from grapes [13] were subject to a forced oxidation procedure [14], the amount of acetaldehyde accumulated was very small, far less than expected. Expectations were based on the common belief that, once SO 2 is depleted, most of the H 2 O 2 formed in the second reduction of O 2 , suffers a catalytic decomposition to form the hydroxyl radical known as Fenton reaction.…”
Section: Introductionmentioning
confidence: 91%